Debate over the “social question” in occupational therapy: an integrative review/O debate sobre a “questão social” na terapia ocupacional: uma revisão integrativa - Munguba, Marilene Calderaro; Malfitano, Ana Paula Serrata; Lopes, Roseli Esquerdo (Cadernos Brasileiros de Terapia Ocupacional, 2018)
Introduction: “Social question” refers to the association between work and its social integration in a capitalist society, assuming a new contemporal configuration. Issues arising from the social question challenge professionals from different fields to provide relevant technical answers. Objective: This study aims to understand how occupational therapists have been addressing topics related to social question in occupational therapy journals indexed on Web of Science database. Method: An integrative literature review was conducted (2000-2014) using journals indexed in Thomson Reuters’ Web of Science containg the term “occupational therapy” in their titles. Overall, 32 descriptors related to social question were used in our review. Results: The review found 186 texts, for which the abstracts were read and filters were applied to focus on the social question. The remaining 53 texts were read in full and used in our analysis. Several occupational therapy academicians have reflected on the social question. Their focus has mainly been on promoting health and wellness. The present review has a scope limitation because it only analyzes English texts indexed in the Web of Science. Conclusion: Occupational therapists should go beyond health interventions in favor of approaching actions that encompass different fields in order to promote greater social participation for all in a globalized capitalist society.